BENDING OF REINFORCING BARS TESTING METHOD AND INFLUENCE ON STRUCTURES - Warsianto, Hari; Narayudha, Moga (TEKNIK, 2009)
Reinforcing bars in concrete elements functions as the component carrying tensile stresses after concretecracking. This is due to that fact that concrete exhibit very high compression strength combined with avery low tensile capacity. The tensile stressed are transferred to the bars by the bond between thereinforcement and the concrete.Bars are generally produced in strands 6 to 12 meter in length so that bending for transportation andhandling purposes becomes necessary. At the site bars are straightened, and then sometimes re-bent forassembling purposes. This process will result in a loading and re-loading of steel.The ASTM E-290 mandated that bars have to pass the bending test, whereas reinforcing steel bars arebend to almost 1800 to ensure material ductility. In the past five years the Construction and MaterialLaboratory, Diponegoro University has been questioned with the issue as to how far this bending andstraightening influences the quality and what the significance of testing is.This paper will evaluate theinfluence of bending and straightening and the testing procedure involved.